Emittance Reduction of RF Photoinjector Generated Electron Beams by Transverse Laser Beam Shaping. (November 2019) - Gross, M; Qian, H J; Boonpornprasert, P; Chen, Y; Good, J D; Huck, H; Isaev, I; Koschitzki, C; Krasilnikov, M; Lal, S; Li, X; Lishilin, O; et al.
Abstract: Laser pulse shaping is one of the key elements to generate low emittance electron beams with RF photoinjectors. Ultimately high performance can be achieved with ellipsoidal laser pulses, but 3-dimensional shaping is challenging. High beam quality can also be reached by simple transverse pulse shaping, which has demonstrated improved beam emittance compared to a transversely uniform laser in the 'pancake' photoemission regime. In this contribution we present the truncation of a Gaussian laser at a radius of approximately one sigma in the intermediate (electron bunch length directly after emission about the same as radius) photoemission regime with high acceleration gradients (up to 60 MV/m). This type of electron bunch is used e.g. at the European XFEL and FLASH free electron lasers at DESY, Hamburg site and is being investigated in detail at the Photoinjector Test facility at DESY in Zeuthen (PITZ). Here we present ray-tracing simulations and experimental data of a laser beamline upgrade enabling variable transverse truncation. Initial projected emittance measurements taken with help of this setup are shown, as well as supporting beam dynamics simulations. Additional simulations show the potential for substantial reduction of slice emittance at PITZ.